1989
DOI: 10.1002/pssb.2221540106
|View full text |Cite
|
Sign up to set email alerts
|

On the Determination of Enhancement Factors of Solvent Diffusion

Abstract: I n dilute binary f.c.c. alloys of the substitutional type a nonlinear increase of the solvent diffusion coefficient DZ by alloying solutes with positive excess charge is frequently observed. The formation of vacancy-impurity complexes leads to this increase, which is usually described in terms of the enhancement factors bi in the following manner: Dz(NB) = D I ( 0 ) (1 + b&B + bzNg + + b,Ng + ...). The determination of enhancement factors by using this polynomial is critically

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The reliability of these high values is not known, but the solvent enhancement coefficients, b2. in several Cu-based systems are also very high (Hoshini, Iijima andHirano 1982, Faupel andHehenkamp 1984). The validity of eqn.…”
Section: Evaluation Of Bimentioning
confidence: 93%
See 1 more Smart Citation
“…The reliability of these high values is not known, but the solvent enhancement coefficients, b2. in several Cu-based systems are also very high (Hoshini, Iijima andHirano 1982, Faupel andHehenkamp 1984). The validity of eqn.…”
Section: Evaluation Of Bimentioning
confidence: 93%
“…(7). Figure 5 Hagenschulte and Heumann (1989) reported that the solvent diffusion enhancement factor can frequently be represented by an exponential relation even over concentration ranges above 2 at.%. As in the case of solvent diffusion, solute diffusion data have been also well represented by a similar exponential equation (Le Claire 1992).…”
Section: Introductionmentioning
confidence: 98%